A Case of van Neck-Odelberg Disease and Intermittent Overuse Injury - İlke BEYİTLER,; Salih KAVUKCU, (Archives of Rheumatology, 2016)
In van Neck-Odelberg disease, an enlarged anatomical structure called ischiopubic synchondrosis is susceptible to mechanical stress which causes delayed ossification of this temporary joint. Features of the disease, particularly if unilateral, may mimic other conditions such as neoplasm, stress fracture, or osteomyelitis. In this article, we present a seven-year-old male patient with right painful ischiopubic synchondrosis which was misinterpreted as a subacute fracture of which its symptoms resolved with rest and analgesics. Three and six months later, he developed patellofemoral pain syndrome on the left leg due to overuse of that contralateral side. Clinicians should be careful when evaluating leg pain on the overused side opposite to ischiopubic synchondrosis.